Tracing the cultural legacy of Irish Catholicism: from Galway to Cloyne and beyond - Maher, Eamon; O'Brien, Eugene (Manchester University Press, 2017)
This book traces the steady decline in Irish Catholicism from the visit of Pope John Paul II in 1979 up to the Cloyne report into clerical sex abuse in that diocese in 2011. The young people awaiting the Pope's address in Galway were entertained by two of Ireland's most charismatic clerics, Bishop Eamon Casey and Fr Michael Cleary, both of whom were subsequently revealed to have been engaged in romantic liaisons at the time. The decades that followed the Pope's visit were characterised by the increasing secularisation of Irish society. Boasting an impressive array of contributors from various backgrounds and expertise, the essays in the book attempt to trace the exact reasons for the progressive dismantling of the cultural legacy of Catholicism and the consequences this has had on Irish society